2014
DOI: 10.5012/bkcs.2014.35.11.3158
|View full text |Cite
|
Sign up to set email alerts
|

Simple Pyrene Derivatives as Fluorescence Sensors for TNT and RDX in Micelles

Abstract: Various pyrene derivatives were synthesized and systematically examined in micelles. Synthesized mono and bispyrene derivatives were tested in micelles so that they displayed a strong excimer band and the excimer band was quenched in the presence of TNT and RDX. In the optimized condition, the binding constant for TNT of a simple dipyrene derivative 4 was increased up to 1.0 × 10 6 M −1 in cetyl trimethylammonium bromide (CTAB) micelles, which allowed for the detection of 2 ppb of TNT and 334 ppb of RDX by flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…Unlike 28, molecular structure analysis of 29 revealed that it does not form such supramolecular polymeric structure due to the lack of required H-bonding interactions. Compounds 28─30 exhibited strong emission in solution with estimated quantum yields of Φ = 0.21 (28); 0.23 (29) and 0.47 (30). The fluorescence quenching titration study of 28─30 with picric acid 5 demonstrated that, as expected, the quenching efficiency followed the order 28>29>30.…”
Section: Anthracene Based Sensorssupporting
confidence: 57%
See 3 more Smart Citations
“…Unlike 28, molecular structure analysis of 29 revealed that it does not form such supramolecular polymeric structure due to the lack of required H-bonding interactions. Compounds 28─30 exhibited strong emission in solution with estimated quantum yields of Φ = 0.21 (28); 0.23 (29) and 0.47 (30). The fluorescence quenching titration study of 28─30 with picric acid 5 demonstrated that, as expected, the quenching efficiency followed the order 28>29>30.…”
Section: Anthracene Based Sensorssupporting
confidence: 57%
“…The fluorescence quenching titration study of 28─30 with picric acid 5 demonstrated that, as expected, the quenching efficiency followed the order 28>29>30. The calculated quenching constants (K SV ) were 2100 M -1 (28); 200 M -1 (29) and 130 M -1 (30). In addition, similar titration study with a series of analytes indicated the largest quenching responses of 28─30 for NACs at 10 ppb level over other analytes BQ, BA, which were elicited poor fluorescence quenching.…”
Section: Anthracene Based Sensorsmentioning
confidence: 75%
See 2 more Smart Citations
“…[28] Gho andc o-authors reported unprecedentedly high binding constants due to the excimer fluorescencequenching by TNT( K sv TNT = 110 6 m À1 )w hile using micellar solutionso ft weezers-like pyrene derivative in semiaqueous conditions. [29] Herein, we report the synthesis and use of water-soluble pyrene derivatives 1-6 for the direct fluorescent detection of common explosives in aqueous solutions. The highs electivity and sensitivity have been confirmed by the enhanced fluorescence quenching of 1-6 in the presence of trace amountso f 2,4-DNT and 2,4,6-TNT.…”
Section: Introductionmentioning
confidence: 99%